Study on solid waste generation among the residential area in Alor Setar, Kedah - Mastura Afnan, Pubin (2018)
Recently, the amount of solid waste generated increase rapidly due to rapid development, increase in population and industrialization. This may lead to uncontrolled environmental problem and need to be given special attention. This research aims to identify the different types of solid waste generated from residential area in Alor Setar, Kedah and to investigate the level of awareness and understanding towards recycling among household. In order to get the amount of solid waste generation, this study is carried out to get the data of waste collection by segregation and weighing of the solid waste from 50 selected houses. The solid waste collected from the samples will be segregate into four components which are household waste, garden waste, bulky waste and household hazardous waste. Other than that, there is about 162 questionnaires that were distributed to get some information about the identification data, solid waste management and public awareness. At the end of data collection, all of the data will be analyzed and all findings from the analysis are being evaluated, discussed and summarized. According to this study, among all four components of waste, household waste (577.67 kg/week) turns to be the highest amount of types of waste that resident discard, which comprises of food waste, plastics, paper, glass, aluminium and others. The second highest types of waste is garden waste with total 19.54 kg/week of production. Next is bulky waste and lastly household hazardous waste with both of waste are 14 kg/week and 10.52 kg/week of production waste respectively. Hence, these studies suggest that the importance of sorting of solid waste at home, effort to improve awareness among resident and practicing to reduce the waste produced in order to preserve the environment and world for our future generation.